PENERAPAN UANG PAKSA DALAM PELAKSANAAN PUTUSAN PENGADILAN TATA USAHA NEGARA PERSPEKTIF SIYASAH SYAR'IYYAH - Wulan Febriyanti Putri Suyanto; Hamzah Hasan; Abdul Rahman Sakka (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The purpose of this study is to find out how the application of forced money as a forced effort in the implementation of decisions in the Pengadilan Tata Usaha Negara Makassar. This type of research is field research using empirical and normative syar'i juridical approaches. Data sources are primary and secondary data obtained through observation, interviews, and documentation. The results showed: 1) The PTUN Makassar has not been able to apply forced money (dwangsom) as an instrument of coercion for the defendant to carry out a judgment that has permanent legal force; 2) The inhibiting factors are caused by the lack of implementing regulations, the absence of executory institutions, and the low awareness of the defendants; and 3) Although not expressly explained in the postulates and history of Islamic constitutionality, the instrument of imposition of forced money became very important and useful in the effort to achieve maslahat, so that its existence did not contradict the principles of siyasah syar'iyyah.